Impediment of Cerebrospinal Fluid Drainage Through Glymphatic System in Glioma - Xu, Dan; Zhou, Jie; Mei, Hao; Li, Huan; Sun, Wenbo; Xu, Haibo (Frontiers in Oncology, 2022)
Background: Cerebrospinal fluid (CSF) plays an important role in maintaining tissue homeostasis in the central nervous system. In 2012, the new CSF outflow pathway, “the glymphatic system” was discovered. The glymphatic system mediates CSF and interstitial fluid exchange through the perivascular pathway, which eliminates harmful solutes in the brain parenchyma. In recent studies, the importance of the glymphatic system has been demonstrated in healthy and neurodegenerative disease brains. However, there is limited research on the function of the CSF in brain tumors. Intracranial hypertension caused by glioma can affect CSF drainage, which impacts the delivery of chemotherapy drugs via intrathecal injection. This study focused on changes in the glymphatic system and the role of aquaporin 4 (AQP4) in glymphatic transport in glioma. Methods: In glioma-bearing rats, the effect of tracer infusion on the intracranial pressure (ICP) was evaluated using an ICP microsensor. In vivo magnetic resonance imaging and ex vivo bright field were used to monitor CSF tracer distribution after cisterna magna injection. AQP4 expression was quantitatively detected, and AQP4 in the astrocytes around the vessels was observed using immunofluorescence. Results: The ICP of the tumor group was higher than that of the control group and the infusion rate of 2µL/min did not affect ICP. In vivo and ex vivo imaging showed that the circulation of CSF tracers was significantly impaired in the tumor. High-power confocal microscopy revealed that in the tumor, the surrounding of AQP4 by Evans Blue was decreased. In both tumor and contralateral areas, data indicated that the number of cluster designation 34 (CD34+) alpha-smooth muscle actin (α-SMA-) veins were more than that of CD34+α-SMA+ arteries. Moreover, in the tumor area, AQP4 in the astrocytes around the vessels was decreased. Conclusions: These findings indicate that the para-arterial influx of subarachnoid CSF is limited in glioma, especially in those with reduced levels of the fundamental protein AQP4. Our results provide evidence toward a potential new treatment method for glioma in the future.